Peran Taman Baca Masyarakat Dalam Meningkatkan Kompetensi Literasi Kesehatan Anak Di Masa Pandemi - Zhafirah, Nurul (Ilmu Informasi Perpustakaan dan Kearsipan, 2022)
This study aims to (1) describe the role of Taman Baca Tanah Ombak in improving health literacy competencies during the pandemic, (2) describe children's health literacy competencies during the pandemic, (3) describe the relationship of the role of Taman Baca Tanah Ombak to children's health literacy competencies during the pandemic. This research uses a type of quantitative research using descriptive methods. The population and samples in this study were children of regular visitors to Taman Baca Tanah Ombak which amounted to 25 respondents. The instrument used in the study was a questionnaire as the main data source. To analyze the data in this study using spearman rank correlation. The results of this study, namely (1) Taman Baca Tanah Ombak has played a very good role based on respondents' responses to 13 items of questions indicators of the role of community reading parks with a score of 3.46 with excellent categories. (2) the competence of children's health literacy – children of visitors to Taman Baca Tanah Ombak has been very well proven based on respondents' responses to 11 items of health literacy indicator questions with a score of 3.33 with a very high category. (3) Taman Baca Tanah Ombak has a significant relationship thanks to the category while Taman Baca Tanah Ombak has a role of 26% while the remaining 74% is influenced by other factors not studied in this study.